2014
DOI: 10.3897/zse.90.7306
|View full text |Cite
|
Sign up to set email alerts
|

Trematodes obtained from the thiarid freshwater snail Melanoides tuberculata (Müller, 1774) as vector of human infections in Thailand

Abstract: Larval stages of trematodes obtained from the freshwater snail Melanoides tuberculata (Cerithioidea, Thiaridae) as intermediate host were studied by using cercarial emergence and crushing snails. Between December 2004 and September 2009 snails from one hundred twenty locations in Thailand were collected every two months for one year at each sampling site. Counts per unit of time method was used in this study, and the samples of snails were collected every 10 minutes per sampling by five collectors. The cercari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 37 publications
7
51
0
Order By: Relevance
“…According to this study, the morphology of the cercaria was found to be similar to that which was described in previous reports [1,15,18]. In recent studies, T. granifera and M. tuberculata have been noted as having a high level of susceptibility for heterophyid cercariae infection [18,30].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to this study, the morphology of the cercaria was found to be similar to that which was described in previous reports [1,15,18]. In recent studies, T. granifera and M. tuberculata have been noted as having a high level of susceptibility for heterophyid cercariae infection [18,30].…”
Section: Discussionsupporting
confidence: 87%
“…Two species of heterophyid trematodes have been identified in this study, namely, H. taichui and H. pumilio, which are known to infect humans and other mammals, and are widely distributed in many provinces of Thailand such as Chiang Mai, Phitsanulok, Mae Hong Son, Kamphaeng Phet, and Tak [10,23,30], as well as in other close countries, like Lao PDR, Korea and Vietnam [2,5,7,16]. A recent study conducted in Lao PDR revealed that many patients were infected with H. taichui, with a 99.8% of the trematode specimens identified in patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…Especially as liver flukes and intestinal flukes human infecting parasites are highly prevalent in Southeast Asian countries (Wongratanacheewin et al 2001, Krailas et al 2014. Infections caused by these flukes have a major public health impact and are also of economic importance in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A checklist from 136 scientific published studies revealed that Melanoides tuberculata could be host for flukes, identified as belonging to 17 families, 25 genera, and 37 species. These trematodes are both animals and human parasites (17), and the presence of various cercariae of Melanopsis snails in some parts of Khuzestan province and their potential to make zoonotic diseases such as heterophyiasis, echinostomiasis and philophthalmiasis in human and animals was previously proved (18). The identification of medically important snails helps to control them.…”
Section: Discussionmentioning
confidence: 99%